2019
DOI: 10.1111/hepr.13397
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable prognosis of patients with acute liver injury due to drug‐induced liver injury and acute exacerbation of hepatitis B virus infection

Abstract: Aim Acute liver injury (ALI) has a favorable prognosis, whereas acute liver failure (ALF) leads to organ failure and thus has an unfavorable prognosis. The effect of each etiology on the clinical course of ALI remains unclear. This study aimed to determine how each etiology and glucocorticoid on the unfavorable etiology affects the clinical course of ALI. Methods This prospective observational study enrolled 522 patients with ALI/ALF from 2004 and 2017. To evaluate the influence of etiology on prognosis, decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…We implemented the referral system for patients with ALI in 2004. Parts of the results have previously been reported by us 3,7,9,16,25,28 . The present observational prospective cohort study was registered in University hospital Medical Information Network (UMIN) in 2015 (UMIN000016568).…”
Section: Subjectssupporting
confidence: 54%
See 4 more Smart Citations
“…We implemented the referral system for patients with ALI in 2004. Parts of the results have previously been reported by us 3,7,9,16,25,28 . The present observational prospective cohort study was registered in University hospital Medical Information Network (UMIN) in 2015 (UMIN000016568).…”
Section: Subjectssupporting
confidence: 54%
“…First, the number of patients was relatively small; therefore, differences between the influence of specific etiologies on the prognosis of SLI remain unclear. We previously reported that the referral system does not decrease the rate of HE development among patients with SLI/ALF due to drug-induced liver disease 16 , nor does it improve the prognosis of patients with exacerbation of hepatitis B 3 ; therefore, the clinical course of each etiology should be carefully observed. Second, the clinical course of the patients in this study does not reflect the natural course of SLI due to the selective population of the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations